Re-entering obesity prevention: a qualitative-empirical inquiry into the subjective aetiology of extreme obese adolescents - Braun, Matthias; Schell, Johanna; Siegfried, Wolfgang; Mueller, Manfred J.; Ried, Jens (BMC Public Health, 2014)
Conclusions: This study contributes substantially to a broader perspective on the prevention of obesity. First, more attention has to be paid to the interactions of medical aspects and the social dimension of obesity. Second, prevention efforts should be more aware of the relevance of subjective aetiology when it comes to the definition of reasonable and effective governance strategies in tackling obesity. Third, current assumptions concerning the importance of personal responsibility for obesity prevention might underestimate the relevance of self-determined action of the obese.
Keywords: Obesity; Prevention; Subjective aetiology; Ethics; Governance; Life-style intervention